Relative Influence of Tillage, Fertilizer, and Weed Management on Weed Associations in Wheat Cropping Systems of Ethiopian Highlands - Kassahun Zewdie; Rungsit Suwanketnikom (Agriculture and Natural Resources, 2005)
Field experiment was conducted at Ambo Plant Protection Research Center of western Ethiopia during 2002 and 2003 to determine the combined effects of tillage, fertilizer and weed management on weed population dynamics in bread wheat (Triticum aestivum L.) field. The results indicated that tillage, fertilizer and weed management systems had a significant effect on weed population dynamics. The total amount of weed density tended to increase in no tillage than conventional tillage or moldboard plow in both years. The magnitude change was ranged from two to four folds when comparing densities in no tillage with others. Among the dominant weeds Polygonum nepalense, Sonchus arvensis, Galinsoga parviflora, Plantago lanceolata, Setaria spp., Echinocloa colona. and Phalaris paradoxa, were significantly reduced in density by moldboard plowing relative to other tillage systems. Tillage had a significant effect on yield in both 2002 and 2003 cropping season. Tank mixture of fenoxaprop-P-ethyl and fluroxypyr +MCPA resulted in a significant reduction of total weed number and increased wheat yield by 40% followed by hand weeding twice. Application of fertilizer increased total broad leaf and grass weed biomass significantly. Fertilizer is more important than tillage in affecting yields and yield components. It improved grain yield up to 48% over the untreated control in both years. Weeding without fertilizer did not affect grain yield. Weeding and fertilizer significantly increased grain yield. The interactions between tillage and fertilizer for total broad leaf weed biomass, grass and broad leaf weed densities were significant. Fertilizer and weed management interaction affects total broad leaf weed density. As far as plant height, grain yield and 1000-kernel weight of wheat are concerned tillage by fertilizer interaction was significant.